Rice supply chain risk mitigation using Fuzzy-AHP: A case study at Bulog’s Warehouse in Malang - Ratutria, Salwa Eugenia; Maulidah, Silvana; Laili, Fitrotul (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
This study aimed to mitigate risks in rice supply chain using the Fuzzy- Analytical Hierarchy Process (Fuzzy-AHP)) approach, focusing on Kebonagung Bulog Warehouse, Malang. With rice being a staple food in Indonesia and increasing consumption, effective supply chain management is critical for ensuring food security. The research identified and prioritizedkey risks faced by actors in the rice supply chain, including supply, quality, storage, and environmental risks. Data were collected through purposive and snowball sampling methods, involving rice processing industries, Kebonagung Bulog Warehouse, and traders. Fuzzy-AHP method was employed to prioritize risks, with supply risk being the highest for rice processors and traders, and quality risk for Kebonagung Bulog Warehouses. Supply risk for rice processors and traders was primarily caused by inconsistent raw material availability due to fluctuating harvest yields and supplier unreliability. Quality risk for Kebonagung Bulog Warehouse occured due to improper handling and prolonged storage, leading to deterioration and reduced rice quality. Risk mitigation strategies include formal partnerships, regular evaluations, strict supplier selection, and improved quality management practices. These findings offer a framework for improving risk management in rice supply chains and enhancing food security in Indonesia.